Nomogram for predicting olfactory disorder in obstructive sleep apnea: A retrospective study based on a multicenter database - Jiajia Dong; Xiao Yu; Yazhu Liang; Honglei Zhang; Haili Sun; Rui Guo (PLoS ONE, 2025)
Objective Obstructive sleep apnea (OSA) increases the risk of olfactory disorder (OD), which may serve as an early warning of adverse health consequences. In this study, we aimed to develop and validate a nomogram for early detection of OD in patients with OSA. Methods We retrospectively analyzed 125 patients with OSA at Beijing Anzhen Hospital for the development and internal validation of the nomogram. For external validation, 30 patients with OSA were recruited from the Air Force Medical Center. The included participants completed polysomnography (PSG) and the Sniffin’ Sticks test. Patients with OSA were divided into two groups: OSA with OD and OSA without OD. Results The nomogram included age, sex, and time spent with oxygen saturation below 90%. The area under the receiver operating characteristic curve of the nomogram was 0.814 (95% confidence interval [CI]: 0.673–0.955) for the internal validation group, and 0.778 (95% CI: 0.601–0.955) for the external validation group. The nomogram exhibited excellent discrimination and calibration, showing substantial benefits in clinical applications. Conclusion The present nomogram developed based on clinical characteristics and PSG features can serve as a convenient tool for clinicians to detect OD in OSA, aiding in patient stratification and personalized treatment.